Antihypertensive drug effects on long-term blood pressure: an individual-level data meta-analysis of randomised clinical trials - Canoy, D; Copland, E; Nazarzadeh, M; Ramakrishnan, R; Pinho-Gomes, A-C; Salam, A; Dwyer, JP; Farzadfar, F; Sundström, J; Woodward, M; Davis, BR; Rahimi, K (BMJ Publishing Group, 2022)
Objective Evidence from randomised trials of pharmacological treatments on long-term blood pressure (BP) reduction is limited. We investigated the antihypertensive drug effects on BP over time and across different participant characteristics. Methods We conducted an individual patient-level data meta-analysis of 52 large-scale randomised clinical trials in the Blood Pressure Lowering Treatment Trialists’ Collaboration using mixed models to examine treatment effects on BP over 4 years of mean follow-up. Results There were 363 684 participants (42% women), with baseline mean age=65 years and mean systolic/diastolic BP=152/87 mm Hg, and among whom 19% were current smokers, 49% had cardiovascular disease, 28% had diabetes and 69% were taking antihypertensive treatment at baseline. Drugs were effective in lowering BP showing maximal effect after 12 months and gradually attenuating towards later years. Based on measures taken ≥12 months postrandomisation, mean systolic/diastolic BP difference (95% CI) between more and less intense BP-lowering treatment was −11.1 (−11.3 to −10.8)/−5.6 (−5.7 to −5.4) mm Hg; between active treatment and placebo was −5.1 (−5.3 to −5.0)/−2.3 (−2.4 to −2.2) mm Hg; and between active and control arms for drug comparison trials was −1.4 (−1.5 to −1.3)/−0.6 (−0.7 to −0.6) mm Hg. BP reductions were observed across different baseline BP values and ages, and by sex, history of cardiovascular disease and diabetes and prior antihypertensive treatment use. Conclusion These findings suggest that BP-lowering pharmacotherapy is effective in lowering BP, up to 4 years on average, in people with different characteristics. Appropriate treatment strategies are needed to sustain substantive long-term BP reductions.